Study comparing the management decisions by IMNCI algorithm and pediatricians in a teaching hospital for the young infants between 0 to 2 months - Agnihotri Bhattacharyya; Sanjay Kumar Saha; Pramit Ghosh; Chitra Chatterjee; Samir Dasgupta (Wolters Kluwer Medknow Publications, 2011)
Integrated management of neonatal and childhood illness (IMNCI) was already operational in many states of India, but there were very few studies in Indian scenario comparing its validity and reliability with the decisions of pediatricians. The general objective of the study is to compare the IMNCI decisions with the decisions of pediatricians and the specific objectives are to assess the agreement between IMNCI decisions and the decisions of pediatricians, to assess the under diagnosis and over diagnosis in IMNCI algorithm in comparison to the decisions of pediatricians and to assess the significance of multiple presenting symptoms in IMNCI algorithm. The study was conducted among the sick young infants presenting in pediatric department from January to March 2009. The IMNCI decision was compared with pediatrician's decisions by percent agreement, Kappa and weighted Kappa with the aids of SPSS version 10. The overall diagnostic agreement between IMNCI algorithm and pediatrician's decisions was 55.56%, (Kappa 0.32 and weighted Kappa 0.41) with 33.33% over diagnosis, and 11.11% under diagnosis. 71.88% young infants with multiple symptoms and 40% with single symptom were classified as red by IMNCI algorithm, which is statistically significant (P=0.004) whereas 56.25% young infants with multiple and 31.76% with single symptom were considered admissible by pediatricians, which is not statistically significant (P=0.052).